Decreases in serum apolipoprotein B-100 and A-I concentrations in cows with milk fever and downer cows - Oikawa, Shin (2002)
Milk fever occurring during the peripartum period has been suggested to be caused by fatty liver developed during the nonlactating stage because diseased cows have increased serum concentrations of non-esterified fatty acids (NEFA) and show hepatic lipidosis. In cows with fatty liver and related diseases such as ketosis, serum concentrations of apolipoprotein (apo) B-100 and apoA-I are decreased. The purpose of the present study was to examine whether apoB-100 and apoA-I concentrations are similarly decreased in cows with milk fever. Apolipoprotein concentrations were also measured in cows with downer syndrome, which has been suggested to be related, at least in part, to milk fever. Compared with healthy cows during early lactation, apoB-100 and apoA-I concentrations were decreased in cows with milk fever and also in downer cows. In cows with milk fever, the decreases in apoB-100 and apoA-I concentrations were associated with increased NEFA and decreased cholesterol and phospholipid concentrations. However, in downer cows, serum lipid concentration changes were not as distinct as in cows with milk fever. These results, coupled with previous findings on the decreases in apoB-100 and apoA-I concentrations of cows with fatty liver-related diseases, suggest that fatty liver is involved in the development of milk fever and partly in that of downer cow syndrome.